Effect of Milling on the Densification of SiC-BasedComposites from Polysilazane - Noviyanto, Alfian; Nishimura, Toshiyuki (UI Scholars Hub, 2016)
High density SiC-based composites from polysilazane were fabricated by high energy milling and hot pressing. After cross-linking at 200 °C, the polysilazane was pyrolysed at 1000 °C in N2 for 2 h to form amorphous Si-C-N-O followed by high energy milling for 1 h. Milled amorphous Si-C-N-O was sintered in hot pressing at 1600 and 1700 °C for 1 h in vacuum under the applied pressure of 50 MPa. Although no sintering additives were used, dense SiC-based composites were obtained with this method. Sintered density was 3.04 g/cm3, while only 2.57 g/cm3 for amorphous Si-C-N-O without milling. It is suggested that the liquid phase generated during the formation of Si2N2O facilitated the densification of the composite.